Virtual learning environments and metacognition: a bibliometric study in the Latin American context (Papeles, 2014)
Information and Communication Technologies started to be used as Virtual Learning Environments (VLE), in the nineties and have become a regular resource in the educational field. Its accelerated development and variety of tools make them high potential instruments able to transform an educational system designed for the industrial society and inconsistent with the requirements of the XXI century, characterized by its emphasis on knowledge and creativity as first order resources. The purpose of the current article is to present the results of a bibliometric study about the Latinamerican research production in the area of Virtual Learning Environments and metacognition, developed in the last eight years and published in three different databases: SciElo, Ebsco y Proquest. Data about number of articles, types of VLE, educational levels and fields in which these researches have been done. Finally, the contributions and future directions of these studies are exposed.
Keywords: metacognition; information and communication technologies; virtual learning environments; bibliometric studies